Will you be my Valentine? - Burke, Diana G.; Copyright Paperback Collection (Library of Congress) (New York : minstrel Books, 2000)
Michelle is determined to find her older sister, Stephanie, the perfect date for the school's Valentine's Day dance.
"A Minstrel book."
"Based on the hit Warner Bros. TV series"--Cover.
"A Parachute Press book."
Keywords: Full house (Television program) -- Juvenile fiction; Valentines Day -- Juvenile fiction; Sisters -- Juvenile fiction; Valentine's Day -- Fiction; Sisters -- Fiction; Children's stories; Radio and television novels